Scaling agroecological packages for soil and water conservation in mixed crop livestock systems in Tunisia - Rudiger, Udo; Frija, Aymen; Alary, Veronique; Idoudi, Zied (International Center for Agricultural Research in the Dry Areas, 2022)
This work shows opportunities and constraints related to the scaling of soil and water conservation technological packages in Tunisia. This poster was delivered during the Tropentag 2022 conference in Prague Czech University of Life Sciences, Prague/Czech Republic: September 14-16